Comparison of Ice Lined Refrigerators of the different types used in Western part of India under the Universal Immunization Program - Modi, Bhautik; Joshi, Krupal; Kokare, Vikas; Singhal, Sanjay; Jasani, Krishna; Parmar, Kamlesh (Indian Journal of Community Health, 2025)
Background & Objective: The effectiveness of Ice-Lined Refrigerators (ILRs) is crucial in maintaining the cold chain for vaccines, particularly in India's Universal Immunization Program (UIP). This cross-sectional study aimed to compare the performance of top-and front-opening ILRs in Gujarat, focusing on temperature stability, holdover time, and functionality. Methods: A total of 123 ILRs from various manufacturers were assessed across urban and rural health facilities. Key parameters such as ambient temperature, breakdown frequency, ease of use, and temperature fluctuations during door openings were recorded. Mann-whitney U test/ t-test and Binary logistic regression model were used as statistical methods. Results: Analysis indicated that top-opening ILRs, which made up 72.4% of the sample, performed significantly better in maintaining temperature stability and had a longer holdover time (mean: 5.4hours) compared to front-opening ILRs (mean: 4.3hours). Temperature breaches were more frequent in top-opening models (34.8%) compared to front-opening ones (5.9%), but the front-opening ILRs exhibited a greater temperature rise during door openings. Logistic regression analysis revealed a strong association between longer holdover time and top-opening ILRs. The study also found infrastructure and training gaps at some facilities, with only 57.7% of ILRs equipped with functional temperature monitoring systems, and many health workers lacking updated training. The findings suggest that top-opening ILRs are more reliable for cold chain management, though further investigation into front-opening models is warranted. Conclusion: For future cold chain management, prioritize top-opening ILRs for their reliability, increase AMC coverage for consistent maintenance, and enhance training for personnel on ILR handling, especially with newer models. Additionally, invest in backup-power and temperature monitoring equipment to prevent temperature breaches, particularly in remote areas.